Application of Merleau-Ponty’s philosophy to nursing qualitative research - Papathanassoglou, Elizabeth; Karanikola, Maria (My University, 2007)
Background: Several philosophies originating from Phenomenology, have provided the background of distinct methodological approaches in nursing research. Purpose: The purpose of the present study is to describe the application of Merleau-Ponty's philosophy to phenomenological research methodology in nursing. Method: A critical narrative review was carried out. Evidence was collected through the MEDLINE and CINHALL databases and the US National Library of Medicine. Books and Published studies from 1982 to 2007 were selected according to pre-specified criteria. Findings: The main concepts of Merleau-Ponty' s philosophy concerning the lived experience of a phenomenon such as embodiment, consciousness, natural attitude, experience and perception constitute the underpinnings for Van Manen's and Munhall's methodology for existential phenomenological research in nursing. The main stages applied within the framework of this methodology are bracketing, intuiting, analyzing, and describing. Conclusions: The application of Merleau-Ponty's philosophy within existential phenomenology may provide reliable and valid research methodology in nursing.
Εφαρμογή της φιλοσοφίας του Merleau-Ponty στη νοσηλευτική ποιοτική έρευνα
Keywords: Methodology; Nursing; Qualitative research; Phenomenology